Prevalence of Ciprofloxacin Resistance among Gram-Negative Bacilli Isolated From Different Specimens at a General Hospital in Riyadh, Saudi Arabia - Hossain, Mohammad Afzal; Mohal, Shirin; Yusuf, Md Abdullah; Islam, Md Saiful; Islam, Md Rafiqul; Roy, Sushmita (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Resistance among the different classes of antimicrobials including fluoroquinolones has arisen in a multitude of bacterial species in the hospitals and in the community. Objective: The purpose of the present study was to measure the prevalence of ciprofloxacin resistance as well as to evaluate the susceptibility pattern of the isolates to various antibiotics. Methodology: This cross sectional study was carried out in the Department of Microbiology at a General Hospital in Riyadh, Saudi Arabia from July'2009 to December'2009. Different clinical specimens were collected and culture was done in the appropriate media. Antibiotic susceptibility testing was performed. Gram negative bacterial isolates with decreased susceptibility to ciprofloxacin were tested for minimum inhibitory concentration (MIC) by using the E-test. Results: A total of 1246 gram-negative bacilli (GNB) were isolated from different specimens of which 486(39.0%) isolates were resistant to ciprofloxacin. The MIC of these isolates ranged from 4 to 32 ?g/ml. Most of the Ciprofloxacin resistant isolates were from urinary tract infections. Conclusion: The prevalence of ciprofloxacin resistance in different specimens is high. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16197 J Shaheed Suhrawardy Med Coll, 2013;5(1):7-10